PENGARUH MEDIA KARTU HURUF TERHADAP KEMAMPUAN MEMBACA PERMULAAN KELAS I SD NEGERI 42 KOTA SORONG TAHUN AJARAN 2023/2024 - Sara M. Bleskadit; Desti Rahayu; Heny Sri Astutik (CV. ADIBA AISHA AMIRA, 2025)
Reading ability is one of the abilities that must be developed at an early age. Language skills enable humans to be able to communicate with each other, whether it is communicating thoughts, feelings or attitudes. The aim of this research is to describe the influence of letter card media on the beginning reading ability of class I at SD Negeri 42 Sorong City for the 2023/2024 academic year. This type of research is quantitative research using experimental methods. The research design used in this research is one group pretest posttest design. This research will be carried out in Class I classes at SD Negeri 42 Sorong City. This research will be carried out on March 4-8 2024. The population of this research is all Class I students of SD Negeri 42 Sorong City, totaling 20 students. The sample used in this research was class I students with a sample size of 20 students. Based on the problem formulation proposed in this thesis and the research data and analysis, it can be concluded that the initial reading ability of the posttest using letter card media in class I is higher than the pretest without using letter card media. Based on the results of calculations using SPSS 21, the pretest results had a mean of 70, while the posttest results had a mean of 78.16 and ???????????????????????? = 1.724 while ????ℎ???????????????????? = 4.375. So that ????ℎ???????????????????? > ???????????????????????? and the significance value is 0.00 < 0.05. So H0 is rejected so it can be concluded that there is an influence of letter card media on the beginning reading ability of Class I of SD Negeri 42 Sorong City for the 2023/2024 academic year.